2013
DOI: 10.4329/wjr.v5.i8.285
|View full text |Cite
|
Sign up to set email alerts
|

3.0 Tesla vs 1.5 Tesla breast magnetic resonance imaging in newly diagnosed breast cancer patients

Abstract: AIM:To compare 3.0 Tesla (T) vs 1.5T magnetic resonance (MR) imaging systems in newly diagnosed breast cancer patients. METHODS:Upon Institutional Review Board approval, a Health Insurance Portability and Accountability Actcompliant retrospective review of 147 consecutive 3.0T MR examinations and 98 consecutive 1.5T MR examinations in patients with newly diagnosed breast cancer between 7/2009 and 5/2010 was performed. Eleven patients who underwent neoadjuvant chemotherapy in the 3.0T group were excluded. Mammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our study featured a prospective design, and interpreting radiologists and research associates conducting quantitative DTI analyses were blinded to the histopathologic results. All breast MRIs in our study were performed at high-field strength (3 T), which has been shown in prior studies to have improved diagnostic performance compared to 1.5 T due to superior signal-to-noise ratio (SNR), which can in turn enable increased spatial resolution [4547]. To increase the robustness of our statistical analysis, we used an advanced machine learning-based LASSO modeling technique, which simultaneously performs variable selection and parameter regularization to limit overfitting, along with bootstrap optimism adjustment to account for training and testing using the same dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Our study featured a prospective design, and interpreting radiologists and research associates conducting quantitative DTI analyses were blinded to the histopathologic results. All breast MRIs in our study were performed at high-field strength (3 T), which has been shown in prior studies to have improved diagnostic performance compared to 1.5 T due to superior signal-to-noise ratio (SNR), which can in turn enable increased spatial resolution [4547]. To increase the robustness of our statistical analysis, we used an advanced machine learning-based LASSO modeling technique, which simultaneously performs variable selection and parameter regularization to limit overfitting, along with bootstrap optimism adjustment to account for training and testing using the same dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral separation of fat and water is better in 3.0-T MRI. Therefore, fat suppression is superior in 3.0-T MRI images and lesion enhancements are more clearly visualized (23). In our study, the number of patients with increased areolar-periareolar skin thickness was statistically significantly higher in patients imaged with 3.0-T MRI than those imaged with 1.5-T MRI.…”
Section: Discussionmentioning
confidence: 43%
“…3.0-T MRI has higher spatial and temporal resolution than 1.5-T MRI (22,23). The evaluation of the morphology of the breast lesions improved with 3.0-T MRI (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Papers regarding breast DWI at 3.0 T are still scarce, but this field strength seems to be advantageous for characterising breast lesions [19][20][21][22]. Image quality is very important, as lesion characterisation and ADC quantification directly depend on the ability to locate it and measure its signal intensity.…”
Section: Discussionmentioning
confidence: 99%